1998
DOI: 10.4269/ajtmh.1998.58.365
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of artesunate and dihydroartemisinin in children with Plasmodium falciparum malaria in Gabon after administration of 50-milligram artesunate suppositories.

Abstract: A thermostable suppository of artesunate (artesunic acid) has been developed. In Gabon, 12 children with Plasmodium falciparum malaria received two administrations of this suppository in a 4-hr interval. Parasitemia and fever were then measured and the plasma levels of artesunate and its active metabolite, dihydroartemisinin, were determined by means of a reversed phase high-pressure liquid chromatography method using reductive electrochemical detection. Substantial parasite clearance (97-100%) was noted 24 hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 6 publications
3
40
0
Order By: Relevance
“…Peak levels of dihydroartemisinin found in Gabonese children after rectal artesunate treatment were 468 nM and therefore far beyond EC values found in the course of this study (9). Peak plasma concentrations for clindamycin are reported to be 17 M in adults after single administration of a 600-mg clindamycin hydrochloride capsule (8).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Peak levels of dihydroartemisinin found in Gabonese children after rectal artesunate treatment were 468 nM and therefore far beyond EC values found in the course of this study (9). Peak plasma concentrations for clindamycin are reported to be 17 M in adults after single administration of a 600-mg clindamycin hydrochloride capsule (8).…”
Section: Discussionmentioning
confidence: 79%
“…Although resistance to artemisinin derivatives was induced in vitro and despite reports of in vivo treatment failure of artesunate, these findings seem to be of limited clinical relevance due to high recrudescence rates when artesunate is used in monotherapy for too short a treatment duration (2,10,11). The development of drug resistance is further curbed by particularly short plasma half lives of both drugs (8,9,17,28). Moreover the sesquiterpene lactones rapidly reduce the parasite load by a factor of approximately 10 Ϫ4 per asexual life cycle (i.e., 48 h) in vivo and are known to inhibit gametocytogenesis to a certain degree, a potential asset for the prevention of propagation of resistance (25,28).…”
Section: Discussionmentioning
confidence: 99%
“…Two study drugs were used: ARS suppositories (Rectocaps; capsules with 200 or 50 mg of ARS; Mepha Pharmaceuticals Ltd.), formulated as described previously (8), and parenteral ARS (Guilin No. 2 Factory, Guangxi, People's Republic of China).…”
Section: Study Design Descriptionmentioning
confidence: 99%
“…ARS is currently formulated for administration by the oral and parenteral routes (3,11). ARS suppositories (Rectocaps; 50 mg of artesunate; Mepha Pharmaceuticals Ltd.) Aesch-Basle, Switzerland) have recently undergone preliminary assessment in Gabonese children (8). However, formal bioavailability studies with this formulation are lacking.…”
mentioning
confidence: 99%
“…Though the IC50 value of these antimalarial drugs on JAR cells (from 6.49-6.96 μg/mL) are higher than the effective antimalarial concentration [plasma level ranging from 0.2-5.0 μg/mL (1,8,21,24)] for treatment, a detrimental effect on the trophoblasts was observed at the lowest dose of the drugs used (3.13 μg/mL). Interestingly, it had been reported that the quinine treatment regimen for patients in Thailand, could lead to a plasma level of quinine as high gression was accompanied by the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%